Checklist of the vascular flora of Wielkopolska (Poland): casual alien species - Jackowiak, Bogdan; Celka, Zbigniew; Chmiel, Julian; Latowski, Karol; Żukowski, Waldemar (Biodiversity: Research and Conservation, 2017)
The list of alien vascular plant species only temporarily occurring in Wielkopolska refers to the previously published list of native and permanently established plants. Together, these two lists document the vascular flora of this region at the beginning of the 21st century. The current list, like the previous one, is a result of critical analysis of both contemporary and historical data, collected since the beginning of the 19th century. All information accessible in herbarium collections, publications and unpublished materials was used. A critical analysis was conducted at the taxonomic, nomenclatural, chorological and habitat levels, based on the verification of negative information not supported by sufficient arguments. The list is presented in an alphabetical order. Information on each species includes: family affinity, life form, geographic and historic status. In cases particularly disputable, the standard characteristic of a species was supplemented with an additional commentary.